ANTIOXIDANT AND HEPATOPROTECTIVE EFFECTS OF ASTRAGALUS ECHINOPS AND ASTRAGALUS LOGOPODIOIDES ETHANOLIC EXTRACTS ON PARACETAMOL-INDUCED LIVER INJURY IN RATS - Foudah, Ahmed I.; Soliman, Gamal A.; Abdel-Rahman, Rehab F.; Alankuş- Çalışkan, Özgen; Yusufoglu, Hasan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Paracetamol (PCM) has an adequate safety profile when taken in normal doses. However, it couldproduce oxidative stress with liver injury when taken in an overdose. Plants of Astragalus genus (F. Fabaceae) are ofwide-spread applications. Astragalus echinops (A. echinops) and Astragalus logopodioides (A. logopodioides) weretested for their potential hepatoprotective activities against liver injury induced by PCM in rats.Material and Methods: Seven groups of rats were used for determination of hepatoprotective activities of the extracts.The normal and hepatotoxic control groups received the vehicle while other groups were treated with silymarin (100mg/ kg), A. echinops (250 and 500 mg/kg) and A. logopodioides (250 and 500 mg/ kg), respectively for seven days.Liver injury was induced on the 5th day by oral dosing of PCM (2g/kg) to all rats except those in normal control group.Moreover, the in vitro antioxidant activities of A. echinops and A. logopodioides extracts were tested using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging.Results: Hepatic enzyme markers as alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase andglutamyl transferase and level of total bilirubin were significantly elevated, while total protein and albumin weredeclined significantly in PCM-exposed animals. The liver antioxidant markers like the activities of superoxidedismutase, catalase and glutathione peroxidase and the levels of reduced glutathione were significantly declined, whilehepatic malondialdehyde levels were significantly increased in PCM alone-treated rats. Administration of A. echinops(250 and 500 mg/kg) and A. logopodioides (500 mg/ kg) extracts prior to PCM, significantly protected against theelevation in the serum activities of hepatic enzymes and bilirubin and reduced oxidative stress. The hepatoprotectiveeffect of both extracts was further confirmed by histological findings in the liver tissue. In addition, both extractsdisplayed in vitro antioxidant activities in a concentration-dependent way.Conclusion: Our results suggest that both extracts protect the liver against oxidative damage and they could be used aseffective hepatoprotectives against PCM induced liver injury.